(untitled) (International Journal of Economics Development Research (IJEDR), 2025)
This study aims to determine and analyze the influence of the work environment and job satisfaction on employee retention at Samsat Buleleng. The research employs a quantitative approach using a survey method through the distribution of questionnaires to a number of employees as the sample. The data analysis techniques used include multiple linear regression analysis, T-test, and the coefficient of determination (R²) test. The results of the study show that, partially, the work environment has a significant influence on employee retention, with a coefficient value of 0.246 and a contribution of 36.2%. In addition, job satisfaction also affects retention with a coefficient of 0.390 and a contribution of 39.0%, indicating that the higher the job satisfaction, the greater the tendency of employees to remain in the organization. Therefore, it can be concluded that the work environment and job satisfaction are two important factors that must be considered by the management of Samsat Buleleng in their efforts to increase loyalty and retain the existing workforce.